Immunization of trout (Salmo trutta) against freshwater pearl mussel (Margaritifera margaritifera) by duck mussel (Anodonta anatina) glochidia - Chowdhury, Motiur (2013)
Freshwater pearl mussel Margaritifera margaritifera is endangered throughout its range of distribution in Europe. In some rivers M. margaritifera may co-occur with the duck mussel Anodonta anatina. Brown trout Salmo trutta serves as suitable fish host for both mussel species. Thus it is possible that exposure of brown trout to A. anatina glochidia might increase resistance of fish against M. margaritifera glochidia. The aim was to test this ‘cross immunity hypothesis’. Brown trout were immunized by duck mussel (Anodonta anatina) glochidia in late May. Then brown trout were challenged by pearl mussel (Margaritifera margaritifera) glochidia in late August after the A. anatina glochidia were developed and dropped off from the fish. The mean number and size of M. margaritifera glochidia were compared between immunized and control fish in 4 different time points over 10 months. Besides of these, effect of marking of fish (fin-clipping), fish length and body side (left vs. right) on glochidia number was also studied. The mean number of attached glochidia was significantly lower in immunized fish than in the unimmunized control fish in the first time point, in September, but not in December, May or June. No effect of immunization on growth (size) of glochidia was observed in any time point. Unexpectedly, right side gills contained more glochidia than left side gills of fish regardless immunization. Fish length had a significant positive effect on glochidial abundance. Fin-clipped fish had less glochidia than non-clipped fish. Result indicates that fin-clipping may activate non-specific immunity that may have given protection against M. margaritifera glochidiosis. Results of the present study suggest that cross immunization by exposer to A. anatina glochidia may not possess a significant threat for M. margaritifera conservation.